A Magnetic and pH-Sensitive Composite Nanoparticle for Drug Delivery. (20th May 2018) - Wang, Xin; Gao, Ziyu; Zhang, Long; Wang, Huiming; Hu, Xiaohong
Abstract : Mild acid response nanocarriers have been intensively attracted interest in the field of drug delivery on the account of the responsive property to abnormal physiological environment as well as the original property to normal physiological environment. However, the drug delivery system lacks capacity of precise localization to abnormal tissue or targeted cells. Therefore, a magnetic and pH-sensitive composite nanoparticle was designed and prepared by double water-in-oil-in-water (W/O/W) emulsion using acetylated β -cyclodextrin (Ac- β -CD) as a dominant material to realize the pH response and Fe3 O4 as a component to realize magnetic response. The surface chemical characteristic was characterized by Fourier-transformed infrared spectroscopy (FTIR) using pure Ac- β -CD nanoparticle as a control and exhibits the typical chemical characteristic of Ac- β -CD. Furthermore, the structural information was tracked by X-ray diffraction (XRD) and thermogravimetric analysis (TG). It was found that composite nanoparticle possessed structural characteristic of both Ac- β -CD and Fe3 O4 . Composite nanoparticle exhibited sphere and two-phase morphology with the diameter of about 200–250 nm depending on their detection method and zeta potential of −12 to −14 mV. More importantly, irreversible pH response property and reversible magnetic responsive properties either in neutral environment or in mild acid environment for the composite nanoparticle were confirmed in the research. Finally, drug loading and release behavior were investigated through preliminary in vitro evaluation.